Non-invasive evaluation of cytokine expression using the cerumen of dogs with otitis externa - Yoon, Ji-Seon; Park, Jinho (Frontiers in Veterinary Science, 2024)
The development of a non-invasive method to analyze cytokine expression in the skin will provide further understanding of inflammatory skin disorders. This study aimed to evaluate cytokine expression in the skin through cerumen swabbing in dogs with otitis externa (OE) and to investigate whether increased cytokine expression in infected OE reflects the inflammatory status of the ear canal. Three groups consisting of control dogs (n = 24), dogs with ceruminous Malassezia OE (n = 25), and dogs with suppurative bacterial OE (n = 15) were included in the study. The concentrations of keratinocyte-derived cytokines including Interleukin (IL)-8/chemokine ligand (CXCL)8, IL-10, IL-6, Tumor necrosis factor (TNF)-α, and IL-1ß in the cerumen of the ear canal of the included patients were analyzed using commercial ELISA kits. Additionally, correlations between cytokine levels and cytology scores (of Malassezia yeasts, cocci/rod-shaped bacteria, and inflammatory cells) were assessed. IL-8/CXCL8 concentrations were significantly higher in dogs with ceruminous Malassezia OE and dogs with suppurative bacterial OE than in control dogs. Furthermore, IL-8/CXCL8 concentrations positively correlated with Malassezia scores in dogs with ceruminous OE (r = 0.630) and with bacterial scores in dogs with suppurative OE (r = 0.601). In addition, increased expression of IL-6 and IL-1ß were detected in dogs with suppurative bacterial OE compared to those with Malassezia OE and control dogs, and showed positive correlation with inflammatory cell scores (IL6; r = 0.520, IL-1ß; r = 0.680). Therefore, keratinocyte-derived cytokines could be evaluated using non-invasive methods such as cerumen swabbing in dogs with OE.